Factors Affecting Voluntary Switching of Public Accounting Firms: What is the Role of Auditor Reputation? - Naibaho, Eduard Ary Binsar; Amanda, Silvisia (Accounting Analysis Journal, 2024)
Purpose : The research examines the effects of audit opinion, company growth, and financial distress on voluntary public accountant firms’ switching, with the auditor’s reputation acting as a moderating variable. Method : Voluntary Public Accountant Firms Switching and Audit Opinion in this study are measured using dummy variables. Company Growth is measured through a proxy of sales changes, and Financial Distress is gauged using the Debt-to-Equity Ratio. The study uses a purposive sampling method and secondary data from 76 companies in the ASEAN 5 region, Japan, and Australia, all falling under the Consumer Staples sector in the S&P Capital IQ, during 2013-2022. The study uses a regression logistic model. Findings : The research indicates that audit opinion, company growth, and financial distress do not significantly impact voluntary public accountant firms’ switching. The study also demonstrates that an Auditor’s Reputation cannot moderate the impact of Audit Opinion, Company Growth, and Financial Distress on Voluntary Public Accountant Firms Switching. Novelty : Employing two periods of auditor switching, each spanning five years, to comprehensively examine the voluntary auditor switching phenomenon.